2019
DOI: 10.29245/2572.942x/2019/5.1253
|View full text |Cite
|
Sign up to set email alerts
|

The Human Leukocyte Antigen (HLA) DRB1*13:02 Allele Protects against Dementia in Continental Western Europe

Abstract: Human Leukocyte Antigen (HLA) Class II DRB1*13 alleles have recently been found to protect against age-related brain deterioration, even in the presence of apolipoprotein E4 (apoE4), 1,2 suggesting a possible protection against dementia.Here we evaluated the association between the population frequency of common DRB1*13 alleles and the prevalence of dementia in Continental Western Europe. Prevalence of dementia in Continental Western Europe was derived from published reports on dementia frequency from the Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…As in our previous studies 16,17 we focused on the following 14 CWE countries: Austria, Belgium, Denmark, Finland, France, Germany, Greece, Italy, Netherlands, Portugal, Norway, Spain, Sweden, and Switzerland.…”
Section: Cwe Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…As in our previous studies 16,17 we focused on the following 14 CWE countries: Austria, Belgium, Denmark, Finland, France, Germany, Greece, Italy, Netherlands, Portugal, Norway, Spain, Sweden, and Switzerland.…”
Section: Cwe Countriesmentioning
confidence: 99%
“…analyses were used to evaluate the association between the population frequency of each the seven HLA alleles above (Table 2), alone and combined, and the prevalence of dementia and Parkinson's disease in Continental Western Europe. Previous analyses 16,17 had documented an exponential relation between dementia prevalence and allele frequency; hence, the prevalences of dementia and Parkinson's disease were natural-log transformed to analyze their relation to allele frequency using linear regression. Pairwise Pearson correlation coefficients were compared by calculating the normal deviate z-statistic 24 .…”
Section: Statistical Analyses Regression and Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in a recent genetic epidemiological study we evaluated the relationship between the population frequency of DRB1*13:02 and dementia prevalence in 14 CWE countries and found that dementia prevalence decreased exponentially with increasing frequency of DRB1*13:02, even after adjusting for the prevalence of apoE4. 3 Remarkably, the population frequency of DRB1*13:02 accounted for 45% of the variance in dementia prevalence. In the 14 countries included in that study 3 , the frequency of DRB1*13:02 ranged from 0.025-0.062, which equates to 5-13% carriers in the respective country population, suggesting that other factors, such as additional protective HLA alleles, may account for the remaining variance in dementia prevalence.…”
Section: Introductionmentioning
confidence: 98%
“…3 Remarkably, the population frequency of DRB1*13:02 accounted for 45% of the variance in dementia prevalence. In the 14 countries included in that study 3 , the frequency of DRB1*13:02 ranged from 0.025-0.062, which equates to 5-13% carriers in the respective country population, suggesting that other factors, such as additional protective HLA alleles, may account for the remaining variance in dementia prevalence. Thus, in the present study, we evaluated the association between other common DRB1alleles and dementia prevalence in the same 14 CWE countries.…”
Section: Introductionmentioning
confidence: 98%